A case of left undescended testis with ipsilateral ectopic kidney - Mitra, Arti; Araujo, Prenoy; Chandak, Unmed (International Surgery Journal, 2018)
Undescended testis is one of the most common congenital anomalies in newborns. Incidence of this is anywhere between 1.6% and 9.0%. The incidence dramatically drops to 0.9-1.8% at 3 months of age. This is due to the spontaneous descent of the testes. The complications of undescended testes are infertility and malignant transformation. A 29-year-old unmarried male patient came to the hospital with complained of absent of left testis within scrotal sac since birth and a left inguinal swelling since 1 year with no other complaints. On examination, the left scrotal sac was empty. The right side scrotum was normal and testis was palpable within scrotal sac. On USG, examination findings were confirmed Left testis seen in relation to lower pole of left kidney in left inguinal region with normal echo texture s/o left ectopic testis. Left kidney in pelvic region at paramedian location with hilum facing anteromedially s/o left ectopic kidney. Early diagnosis and surgical intervention is key so as to preserve the undescended testis and prevent malignant change or infertility problems. It is imperative that all tests be done to assess kidney function.